AUDIT SISTEM INFORMASI MENGGUNAKAN FRAMEWORK ITIL V3 PADA SISTEM INFORMASI AKADEMIK PERGURUAN TINGGI SWASTA - Rini Nurlistiani (LPPM Universitas Muhammadiyah Kotabumi, 2021)
Collage is a scientific institution that has the task of providing education and teaching above the secondary level, and which provides education and teaching based on the Indonesian national culture and in a scientific way. A good university must be able to utilize IT in carrying out academic and non-academic activities. One example of the use of IT needed in a university is the Academic Information System (SIAKAD) which is expected to help smooth information technology, especially academics. The use of SIAKAD must also be reviewed in terms of network connections, system security, access rights according to user needs, and how system developers evaluate existing business processes and infrastructure. In implementing a good SIAKAD, it is necessary to carry out an important information system audit to improve the performance of this system. The academic information system audit model can be carried out using the Information Technology Infrastructure Library (ITIL) version 3 as a framework to have better.